Yield and vegetative growth of cactus pear at different spacings and under chemical fertilizations - João A. da Silva; Sérgio L. R. Donato; Paulo E. R. Donato; Evilasio dos S. Souza; Milton C. Padilha Júnior; Ancilon A. e Silva Junior (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective was to evaluate the effect of different spacings and mineral fertilizations on cactus pear growth and production in a randomized block design, with three replicates, in a 3 x 4 factorial scheme: three spacings, 1.00 x 0.50 m, 2.00 x 0.25 m and 3.00 x 1.00 x 0.25 m, and four fertilizations, 000-000-000, 000-150-000, 200-150-000 and 200-150-100 kg ha-1 of N, P2O5 and K2O, respectively. Plant growth was evaluated between 90 and 390 days and production and growth were evaluated at 620 days after planting. There were significant interactions between spacing and fertilization for plant height, number of cladodes and cladode area index from 90 to 390 days and for production of fresh and dry matter at 620 days after planting. Spacing influenced cladode area index, while fertilization influenced plant height, number of cladodes and cladode area index at 620 days after planting. Plant height showed cubic effect for the days after planting. Number of cladodes and cladode area index were dependent on spacing, fertilization and plant age, and fitted to cubic models. The best results of growth and production of fresh and dry matter are associated with NPK and NP fertilizations and the spacing of 1.00 x 0.50 m.